HIBAH ORANG TUA KEPADA ANAK MENURUT PERSFEKTIF HUKUM PERDATA DAN HUKUM ISLAM PADA MASYARAKAT DI KELURAHAN BETUNGAN KOTA BENGKULU - Yuvita, Yuvita (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
This research  raises the problem  about  the implementation of parent  grants to children between  justice and  equity in urban  village of Bengkulu.  This research  method using qualitative  research  method. The results of this study concluded that the implementation of parental grants to children in the perspective of civil law in the community in Betungan Village Bengkulu City has implemented a grant in accordance with article 1667  contained in the Book of Civil Law, an agreement, with which a grantee  deliver a good Free of charge,  without being able to withdraw it, for the benefit of a person  who received the delivery of the merchandise. The law only recognizes grants among  the living. (KUHPerd 170, 172ff., 179, 913, 1314,  1675,  1683,  1688.). Implementation of parent  grants to children  in the perspective of Islamic law in the community in Betungan Village Bengkulu City, Implementation of grants conducted by the community in Betungan Village has been  implemented well, and  follow the rules in accordance with the provisions.  Being fair and  equating giving to children  is obligatory.  Doing tafdhil (exaggeration) is forbidden, except  when  there  are factors that allow it. It is permissible  to treat others  against  fellow children if there  are any exclusionary  factors justified in the case  of a disability that makes  a person  unable  to work in search  of a livelihood  such as paralysis, blindness,  inability to work, to seek knowledge  and others